Art of the ordinary : the everyday domain of art, film, philosophy, and poetry - Deming, Richard, 1970- (Cornell University Press, 2018)
"In Art of the Ordinary, Deming brings together the arts, philosophy, and psychology in new and compelling ways so as to offer generative, provocative insights into how we think and represent the world to others as well as to ourselves"--